2009
DOI: 10.1016/j.jaci.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Combined sensitization of mice to extracts of dust mite, ragweed, and Aspergillus species breaks through tolerance and establishes chronic features of asthma

Abstract: Background-Existing asthma models develop tolerance when chronically exposed to the same allergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 41 publications
6
89
0
1
Order By: Relevance
“…We investigated the pERK1/2 staining pattern in a mouse model of chronic asthma where we repeatedly exposed mice to three different allergens, dust mites, ragweed, and Aspergillus (DRA), 2 days a week for 8 weeks and then rested them for 3 weeks. We reported the persistence in this model of peribronchial inflammation, airway remodeling with epithelial hypertrophy, and airway hyperreactivity, which lasted longer than 3 weeks after the last allergen exposure (13). Immunofluorescence studies of the airway tissue from this model demonstrated significant pERK1/2 staining of airway epithelium and inflammatory cells (Fig.…”
Section: Establishing Erk1/2 Bistability and Sustained Activationmentioning
confidence: 56%
“…We investigated the pERK1/2 staining pattern in a mouse model of chronic asthma where we repeatedly exposed mice to three different allergens, dust mites, ragweed, and Aspergillus (DRA), 2 days a week for 8 weeks and then rested them for 3 weeks. We reported the persistence in this model of peribronchial inflammation, airway remodeling with epithelial hypertrophy, and airway hyperreactivity, which lasted longer than 3 weeks after the last allergen exposure (13). Immunofluorescence studies of the airway tissue from this model demonstrated significant pERK1/2 staining of airway epithelium and inflammatory cells (Fig.…”
Section: Establishing Erk1/2 Bistability and Sustained Activationmentioning
confidence: 56%
“…We used the published triple-allergen (DRA)-induced allergic mouse asthma model with minor modifications (19) to recapitulate the pathophysiologic features of SBP-AG of human patients with asthma. Additional detail on the method for the DRA triple-allergen asthma model is provided in the online supplement and Figure E2.…”
Section: Dra Triple-allergen Asthma Modelmentioning
confidence: 99%
“…We subjected mice to sensitization and challenge with a combination of house dust mite, ragweed, and Aspergillus allergen (DRA), as previously described, with minor modifications (19).…”
Section: Increasedmentioning
confidence: 99%
“…Some other studies also achieved sensitization to co-administered antigens after only 1 or 2 challenges. They differ from our study by the fact that the antigens were given intranasally and in high amounts [20,21,26]. In the one study most comparable to ours [21], 100 µg of ragweed protein was given intranasally to OVA-primed mice, together with 20 µg of OVA, in order to induce Th2 spread to the ragweed proteins.…”
Section: Discussionmentioning
confidence: 61%